EFISIENSI UNIT ODOR ELIMINATOR DALAM MENGURANGI KONSENTRASI AMONIA (NH3) PADA INSTALASI PENGOLAHAN AIR LIMBAH DOMESTIK - Tri Lestari, Ni Ketut Delvia; Purnama, I Gede Herry (ARCHIVE OF COMMUNITY HEALTH; Vol 9 No 3 (2022): Desember 2022, 2022)
ABSTRACT Domestic wastewater is generated from human activities. Domestic waste treatment must be carried out, both waste generated from businesses and other activities that produce domestic waste. This is regulated in Minister of Environment and Forestry Regulation No.68 of 2016 in article 3 paragraph 1. One of the widely used wastewater treatment systems is the Anaerobic Baffled Reactor (ABR) system. Wastewater treatment with this system produces a by-product in the form of gas that has an unpleasant odor and has a negative impact on human health. Currently, the method to reduce the gas concentration has been widely used and developed. Therefore, this study aims to determine the efficiency of the odor eliminator unit as a gas purification tool, in reducing the concentration of amonia (NH3) produced from wastewater treatment. This study uses a quantitative descriptive approach with pretest and posttest designs. The results showed that the odor eliminator unit efficiency was 72,785% at location A, 89,873% and 89,927% at locations B and C and the highest efficiency at location D was 97,499%. Overall the average concentration of amonia (NH3) at the odor eliminator outlet is below the threshold value of the odor level quality standard. Keywords: Amonia (NH3), Odor Eliminator, Anaerobic Baffled Reactor